Adoption of e-publishing amongst Malaysian journal publishers / Sanni Shamsudeen Ademola - Ademola, Sanni Shamsudeen (2014)

(untitled)
The study investigates adoption of e-publishing amongst Malaysian journal publishers through the lenses of the Diffusion of Innovation Theory. The main objectives of the study are to: (i) Determine the relevance of organizational variables and publishers characteristics in the adoption of e-publishing amongst Malaysian journal publishers. (ii) Identify key attributes and factors that are most relevant in the adoption of e-publishing amongst Malaysian journal publishers. (iii) Evaluate the diffusion rate of e-publishing amongst Malaysian journal publishers. (iv) Examine the level of implementation of e-publishing amongst Malaysian journal publishers. Quantitative research method was adopted using survey questionnaire as the data collection tool and SPSS software for statistical analysis. The participants are Chief Editors or managers of journals published in Malaysia with a total of 156 respondents. The study adopts the Innovation Diffusion Model for the e-journal publishing research framework, by studying and explaining the effect of adopter characteristics variables : field of publishing, publishing experience, publication age, publication size; familiarity and innovativesness; the five attributes of innovation : relative advantage, compatibility, complexity, observability and trialability; two supporting variables: peer network influence and change agent influence as antecedents to the adoption of e-journal publishing amongst Malaysian journal publishers. The study indicates a statistically significant association between field of publishing and publication format X2 (1, n = 140) =.207, P = .050, phi = .207 with publishers in science/technology field adopting e-publishing earlier and in large proportion than their counterparts in social science/arts/humanities. The finding reports that organizational variables or publishers characteristics are not relevant in the familiarity with e-journal publishing and adoption of e-journal publishing. Innovativeness is significantly associated iii with familiarity with e-journal publishing but is not significantly associated with adoption. The most significant attributes in the adoption of e-journal publishing are: relative advantage, complexity, and compatibility, while observability and trialability are moderately significant compared to the first three. The study further indicates a significant but weak relationship between peer network influence and adoption and no relationship between change agent influence and adoption. Meanwhile, the study observed a difference in the relationship between the independent variables and adoption with respect to field of publishing, indicating that there is a field factor in the diffusion process. The findings show that diffusion of e-journal publishing is very low amongst Malaysian journal publishers. The average (mean) year of adoption is 2.33 years with a standard deviation of 3.00. It was observed that many of the publishers who have adopted e-publishing have failed to effectively implement it and the current state of e-journal publishing amongst Malaysian journal publishers is still at the persuasion stage in the innovation decision process. The study is relevant to research in journal publishing, innovation diffusion studies, technology adoption, social and behavioral studies.